The effect of 12-week core strength training on dynamic balance, agility, and dribbling skill in adolescent basketball players - Weiwei Feng; Feng Wang; Yan Han; Gui Li (Heliyon, 2024)
Purpose: The purpose of the study was to examine the impact of core strength training on the dynamic balance, agility, and dribbling ability of adolescent basketball players. Methods: A randomized controlled between-subjects design was employed. Forty-four male adolescent basketball players (aged 14.41 ± 3.22 years) were randomly divided into two groups: the core strength training (CST) group and the conventional training (CT) group. The CST program included 1-h sessions, three times/week for 12 weeks. In contrast, the CT group provided a thorough physical training program that targeted general conditioning rather than focusing solely on core strength. Three measurements were used to evaluate performance in players: the Star Excursion Balance Test, the Illinois Agility Test, and the Dribbling Test conducted at T0 (week 0), T1 (week 6), and T2 (week 12), respectively. Results: Compared to the CT group, the CST group showed a greater improvement (p < 0.05) in dynamic balance, particularly in the anterior, posteromedial, and posterolateral directions, with significant interaction effects (p < 0.05) observed in these measures. Additionally, Bonferroni post-hoc revealed that the CST group demonstrated notably better agility (p < 0.05) at T2; whereas, improvements in dribbling skills were significant (p < 0.05) within the CST group from T1 to T2, but not when compared to the CT group (p > 0.05). Conclusion: The 12-week CST program significantly improved dynamic balance, agility, and dribbling skills in adolescent basketball players, demonstrating its potential as a valuable training component. Future research should explore CST's impact on other sport-specific elements and its applicability to female players.